PELATIHAN DAN PENDAMPINGAN PENGOLAHAN LIMBAH KOTORAN SAPI POTONG MENJADI PUPUK KOMPOS PADA KELOMPOK TERNAK DI KABUPATEN PURBALINGGA - Yuliandri, Lili Adam (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Improper management of cattle manure waste often poses significant challenges for farmers, both in terms of economic losses and negative environmental impacts. This community service program aimed to provide training and assistance to the Maju Makmur Livestock Group in Pagedangan Village, Bojongsari District, Purbalingga Regency, to enhance their knowledge in processing beef cattle manure into economically valuable compost fertilizer. In collaboration with the Purbalingga District Agriculture Office, the program focused on improving farmers’ knowledge and skills in efficient waste processing, as well as developing marketing strategies for compost fertilizer as an additional source of income. Beyond economic benefits, the program also sought to improve environmental health by reducing pollution resulting from unmanaged livestock waste. The activities implemented with the Maju Makmur Livestock Group demonstrated positive outcomes in increasing members’ knowledge and skills through educational and collaborative approaches. The next stage of the program involves conducting chemical analyses of the compost fertilizer to determine nutrient content such as nitrogen (N), phosphorus (P), potassium (K), as well as C-organic levels and pH, designing informative and attractive product labels, and promoting marketing digitalization as an adaptive strategy in the era of modern agriculture.